2012
DOI: 10.1063/1.3677324
|View full text |Cite
|
Sign up to set email alerts
|

A high accuracy femto-/picosecond laser damage test facility dedicated to the study of optical thin films

Abstract: A laser damage test facility delivering pulses from 100 fs to 3 ps and designed to operate at 1030 nm is presented. The different details of its implementation and performances are given. The originality of this system relies the online damage detection system based on Nomarski microscopy and the use of a non-conventional energy detection method based on the utilization of a cooled CCD that offers the possibility to obtain the laser induced damage threshold (LIDT) with high accuracy. Applications of this instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…Further details on the experiment can be found in Ref. [17]. For the following analysis, the respective LIDT values are normalized to the maximum of the calculated field intensity.…”
Section: Deposition Process and Lidt Measurementsmentioning
confidence: 99%
“…Further details on the experiment can be found in Ref. [17]. For the following analysis, the respective LIDT values are normalized to the maximum of the calculated field intensity.…”
Section: Deposition Process and Lidt Measurementsmentioning
confidence: 99%
“…In the case of subpicosecond laser systems, the effect of irradiation conditions (fluence, pulse duration, wavelength, number of pulses, and environment) [1][2][3][4], design and manufacturing conditions (coating process, materials, electric-field distribution) [5,6] were thoroughly studied. Overall, it has been demonstrated that the laser damage resistance of an optic in the subpicosecond regime is both limited by its intrinsic properties (linked to its electronic structure) [7,8] and by the presence of embedded defects induced by the manufacturing process [4,9]. The densities of such embedded defects can be as high as two hundreds of defects∕cm 2 , estimated from the measurement of damage densities during rasterscan tests [10].…”
mentioning
confidence: 99%
“…Laser damage experiments are carried out with the setup described in [8]. The wavelength during this experimental study is 1030 nm.…”
mentioning
confidence: 99%
“…The system is described in details in Ref. [12] and [13]. In these experiments the laser beam was focused on the entrance surface of the tested sample with an anti-reflected coating plano-convex lens.…”
Section: Experimental Set-upmentioning
confidence: 99%